Children performing identical gestures - Unknown:::Creator::::::::::::
Photograph is from a contact sheet and shows four children standing and trying to perform identical gestures. Three of them have one arm raised and that hand is closed in a fist. All four of them have the other arm folded across their torsos. There are windows in the background.